Rotational versus glide technique in elite shot put: Trend analysis in the 21st century - Salinero, J. J.; Del Coso, J. (Journal of Human Sport & Exercise, 2022)
Objective. The aim of this study was to analyse the trend in the use of rotational vs. glide shot-put techniques in World Championships in the last two decades and their association with shot-put performance. Methods. The technique used, and the throwing distance obtained by the finalists in the shot-put competitions (56 men and 55 women) in the World Championships between 2001 to 2019 were analysed. Results. In men, the use of the glide technique was less frequent than in women (30.6 vs. 87.7%; p < .01). In men, there has been a progressive reduction in the use of the glide technique (from 7 out of 10 shot putters in Paris in 2003 to 0 out of 12 shot putters in Doha in 2019). Although a similar tendency is observed in women athletes, the glide technique is still the principal style employed by women throwers (7 out of 12 women shot putters in Doha 2019). Throwing distance was similar between glide throwers and rotational shot putters in both men (20.66 ± 0.67 vs. 20.92 ± 0.88 m; d = 0.32; p = .128) and women athletes (18.85 ± 0.91 vs. 18.75 ± 0.71 m; d = 0.10; p = .753). In summary, the use of the rotational style in shot-put has increased in men athletes. A clear trend towards the use of the rotational technique is also present in women although the glide style is still the most prevalent. However, there are no differences in shot-put performance between techniques that justify the use of the rotational over the glide technique.